Mycobacterium Other Than Tuberculosis (MOTT) – A Case Report - Alsulami, Hosam Abdullah; Ben Salah, Sonia Mezghani (Journal of medical and pharmaceutical sciences, 2020)
Patients with chronic obstructive pulmonary disease (COPD) and bronchiectasis are considered at risk of non-tuberculous mycobacterial lung disease especially those on inhaled corticosteroids. We described a case of a 69-year-old male, Ex. a heavy smoker with past history of pulmonary tuberculosis, COPD with diffuse centro lobular emphysema; status post left thoracotomy for hydropneumothorax, left-sided bullectomy done 8 months back. Patient admitted in our hospital " King Fahad General Hospital, Jeddah " with a history of chronic productive cough with an increased SOB, on/ off fever, night sweats and loss of weight in the last 3 months. No hemoptysis. On examination, he was conscious, oriented, afebrile, positive clubbing. Vitally stable. Chest examination showed a scare of left thoracotomy clean with small chest wall bulge; decreased breath sounds with bilateral ronchi and dullness in the left lower chest. Laboratory investigations showed hyperleukocytosis of 14.6 and serology for HIV was negative. CT scan chest showed left lobulated pleural effusion with empyema necessities, a diffuse emphysematous lung disease with bilateral thick wall cavities and pulmonary nodules as well as left bronchiectasis changes with underlying consolidation collapse. US-guided left pleural aspiration done showed exudative polymorph inflammation. Pleural fluid AFB and PCR was negative and two samples of AFB sputum were positive (2+), PCR was negative, 2 Bactec cultures were positives with the rapid growth of MOTT. Mycobacterial Avium Complex has been identified (Mayoclinic lab. in USA) which is sensitive to Rifampicin*, Clarithromycin* and Ethambutol* but resistant to Moxifloxacin and to Linozelid*. Patient treated with a combination of Rifampicin + Ethambutol* +Clarithromycin* for 18 months with clinical and radiologic improvement and good tolerance. This Study is a "case report study" aimed to report a very rare case, to report a new case of MOTT in Saudi Arabia for the purpose of statistics and for scientific benefit.